ANALISIS MENAJEMEN FLEET PADA KEGIATAN PENGUPASAN OVERBURDEN PT. ARTAMULIA TATAPRATAMA DI DESA TANJUNG BELIT, KECAMATAN JUJUHAN, KABUPATEN MUARO BUNGO - Fadel Rahman; Sumarya Sumarya; Dedi Yulhendra (Journals Mining Engineering : Bina Tambang, 2018)
PT.Artamulia Tatapratama is a company engaged in the field of coal mining. PT.Artamulia Tatapratama is located at Tanjung Belit Village, Jujuhan District, Muaro BungoRegency.In the overburden hauling process to the disposal area there is a dumptruk queue atsome point of the road and long stand by time on the loader, this can cause the loader andhauler productivity to be small so that the production target of 1.190.838 bcm / monthoverburden is not reached. This incompetence is due to a combination of unsuitable toolscausing the occurrence of a waiting gateway or a queue of loads when it is loaded by aloading device. One way to achieve the production targets is required appropriate fleetmanagement.Based on the theory of queue, the waiting time for the conveyance at the time will beloaded is 13.62 minutes on fleet 1, 22.88 minutes on fleet 2 and 14.58 minutes on fleet 3.Fleet setting based on the queue theory is 1 unit PC 1250 serving 6 units of HD 465 on fleet1, 1 unit PC 1250 serving 4 units of HD 465 on fleet 2, 1 unit PC 1250 serving 5 units of HD465 on fleet 3.